From trait affect to situated performance of change-oriented organizational citizenship behavior: the pathway through situational construal and emotion utilization - Zampetakis, Leonidas A.; Arvanitis, Alexios (Frontiers in Organizational Psychology, 2024)
Prior studies indicate that fostering change-oriented organizational citizenship behavior (OCB-CH) among employees, wherein they actively contribute to the collective welfare of modern organizations, correlates positively with their positive affect. However, the precise mechanisms linking trait positive affect with OCB-CH remain unclear. This study used aggregated five-day daily diary data from a sample of 236 full-time employees in Greece to examine positive affectivity differences in the characteristics of situational experiences and how these differences relate to employee OCB-CH via the use of emotions to facilitate performance. Employing multilevel structural equation modeling, the findings revealed a positive association between trait positive affectivity and the situation characteristics of duty, intellect, and positivity, from the DIAMONDS taxonomy. Furthermore, it was determined that perceptions of situational characteristics and emotional utilization sequentially mediated the relationship between positive affectivity and OCB-CH. This study enhances our understanding of how employee trait positive affectivity influences the manifestation of positive change in the form of OCB-CH within organizations.